Electrochemical Studies on Mixed Ligand Complexs of Lead Ion with DL-3(3,4-Dihydroxy Phenyl) Alanine and Some Dicarboxylic Acids - Kumar Singh, Sudesh; Singh Chandel, C.P. (Asian Journal of Chemistry, 2010)
Stability constants of the mixed ligand complexes with Pb(II), viz., Pb(DOPA)(dicarboxylate), Pb(DOPA)(dicarboxylate)2 and Pb(DOPA)2(dicarboxylate) have been determined electrochemically at 30±1ºC and ionic strength of 1.0 M. DOPA = 3(3,4-dihydroxy phenyl) alanie. For the comparison of the stability of simple and mixed complexes, the mixing constant (Km) and the stabilization constant show that the ternary complexes are more stable than the binary complexes.